Impaired Local and Long-Range Brain Connectivity and Visual Response in a Genetic Rat Model of Hyperactivity Revealed by Functional Ultrasound - Droguerre, Marine; Vidal, Benjamin; Valdebenito, Marco; Mouthon, Franck; Zimmer, Luc; Charvériat, Mathieu (Frontiers in Neuroscience, 2022)
Attention-Deficit hyperactivity disorder (ADHD) is a CNS disorder frequently associated with other psychiatric disorders. Pathophysiology processes at stake in ADHD are still under investigation and interestingly neuro-imaging data pointed out to modulated brain connectivity in patients. The genetic spontaneously hypertensive rat (SHR) model has been widely used to study pathophysiological underpinnings of ADHD and resting-state brain connectivity using functional magnetic resonance imaging. Here, functional ultrasound imaging, a new technique enabling fast measurement of cerebral blood volume (CBV), was used to further characterize resting-state functional connectivity – at both local and long-range – and visual response in SHR. We demonstrated that response to visual stimulation was increased in SHR in the visual cortex and the superior colliculus. They displayed altered long-range functional connectivity between spatially distinct regions. SHR also displayed modulated local connectivity, with strong increases of regional homogeneity in parts of the motor and visual cortex, along with decreases in the secondary cingulate cortex, the superior colliculus and the pretectal area. As CBV is intricately coupled to cerebral activity, these results suggest an abnormal neural activity in the SHR animal model, consistent with previous clinical studies and demonstrate the potential of functional ultrasound imaging as a translational tool in ADHD.